The Association of Intelligence Quotient with Obesity and Some Related Factors in Children Girls - Abiri, Behnaz; Vafa, Mohammadreza; Sarbakhsh, Parvin; saleck, Leila; Mousavi, Elnaz; Amiri, Fatemehsadat; Amiri, Zohreh (Progress in Nutrition, 2018)
Background & aim: Childhood obesity is a major public health challenge and a leading cause of various chronic diseases, and reducing the quality of life. Some studies have shown that obesity may harm both the body and the brain. The aim of this study is to investigate the association of Intelligence Quotient (IQ) with obesity and some related factors in children girls in Tehran. Methods: In this cross-sectional study, a total of 286 students (143 obese and 143 non-obese) in the first grade of primary school (aged 6-7 years) were chosen randomly from 19 regions of the ministry of education, from Tehran city. Variables consist of anthropometric indices, dietary intakes, physical activity level, IQ, and some socioeconomic factors were assessed. Statistical analysis was performed using SPSS-V 23 software. Results: There was no statistically significant difference between the obese (ob) and non-obese (non-ob) groups for the total score of IQ (IQob: 97.11±11.1 and IQnon-ob: 95.94±11.9; P= 0.43). In both obese and non-obese groups, there was no significant relationship between IQ with fat mass percentage (FM%) (Pob= 0.939, Pnon-ob= 0.729) and fat free mass percentage (FFM%) (Pob= 0.969, Pnon-ob= 0.729). Also, for the total sample, there was no significant relationship between Body Mass Index and IQ (P= 0.186). Moreover, in both groups, neither dietary intakes of total energy (Pob= 0.978, Pnon-ob= 0.386), fat (Pob= 0.637, Pnon-ob= 0.223), carbohydrate (Pob= 0.541, Pnon-ob= 0.701), or protein (Pob= 0.921, Pnon-ob= 0.476) intake nor physical activity (Pob= 0.144, Pnon-ob= 0.319) has significantly been related to IQ. But in both groups, IQ was positively associated with parent’s education level and also there was positive relationship between economic status and IQ (P